Polar Research: reflections two years after the journal’s transition to open access - Goldman, Helle (Septentrio Conference Series, 2014)
Established in 1982, Polar Research is the English-language, peer-reviewed, scientific journal of the Norwegian Polar Institute (part of the Ministry of the Environment). Until the end of 2007, it was published by the institute on its own. From 2008 through 2010 it was published in partnership with Blackwell as a toll-access journal. At the beginning of 2011 Polar Research became an all open-access, electronic-only journal, published in partnership with the specialized open-access publisher, Co-Action Publishing. Polar Research is the first (to our knowledge, still the only) important international polar journal to become completely open access. Aimed particularly at the editors and managers of other journals considering making a similar transition, this presentation reflects on Polar Research’s conversion to open access, sharing practical lessons learned during the process and outlining the benefits incurred so far.